(untitled) (Papeles, 2026)
Introduction: This article addresses the challenges faced by upper-secondary virtual education programs in their efforts to foster socioemotional development in high school students in Mexico. This is a country with an educational lag of approximately 20 years, according to results from the Programme for International Student Assessment (PISA) and a reported high gap in mental and mood disorder care by the Panamerican Health Organization (Organization for Economic Cooperation and Development [OECD], 2023). Methodology: The study was conducted using a qualitative approach, through an exploratory and descriptive documentary review of academic publications, institutional reports, and current educational regulations in Mexico. Results and Discussion: We analyzed vulnerability factors coinciding with healthy adolescent development, such as neurodivergence. We identified significant structural conditions that hinder the full exercise of the constitutional right to education and examined the institutional and pedagogical challenges present in publicly funded programs adapted to non-traditional modalities, such as the virtual format. Conclusions: The research concludes that to guarantee comprehensive, equitable, and inclusive education, it is necessary to rethink the paradigms of virtual education from an emotional and humanizing perspective. Finally, proposals are highlighted for designing and implementing virtual intervention strategies in public institutions of this educational level, addressing all these challenges at the institutional and curricular levels.